Micromorphology analysis and bond strength of two adhesives to Er, Cr:YSGG laser‐prepared vs. Bur‐prepared fluorosed enamel. Issue 10 (8th July 2014) - Shafiei, Fereshteh; JOWKAR, Zahra; Fekrazad, Reza; Khalafi‐nezhad, Abolfazl
ABSTRACT Preservation of enamel during composite veneer restorations of fluorosed teeth could be achieved by conservative preparation with Erbium lasers. This study evaluated the effect of fluorosed enamel preparation with Er, Cr:YSGG vs. conventional diamond bur on the micromorphology and bond strength of a self‐etch and an etch‐and‐rinse adhesives. Er, Cr:YSGG laser or diamond bur preparation was performed on the flattened midbuccal surfaces of 70 extracted human premolars with moderate fluorosis (according to Thylstrup and Fejerskov index, TFI = 4–6). Adper Single Bond (SB) with acid etching for 20 or 40 s and Clearfil SE Bond (SEB) alone or with additional etching was applied in four laser groups. The same adhesive procedures were used in three bur groups except for 40 s of etching along with SB. After restoration, microshear bond strength was measured (MPa). Data were analyzed using ANOVA and Tamhane tests (α = 0.05). Six additional specimens were differently prepared and conditioned for scanning electron microscopy evaluation. The highest and lowest bond strengths were obtained for bur‐prepared/SB (39.5) and laser‐prepared/SEB (16.9), respectively, with a significant difference (P = 0.001). The different adhesive procedures used associated to two adhesives exhibited insignificantly lower bonding in laser‐prepared groups compared to bur‐prepared ones (P > 0.05), with the exception of additional etching/SEB, which bonded significantly higher to bur‐prepared (36.4) than to laser‐prepared enamel (18.7, P = 0.04). Morphological analyses revealed a delicate etch pattern with exposed enamel prisms on laser‐prepared fluorosed enamel after acid etching and less microretentive pattern after self‐etching primer. The etch‐and‐rinse adhesive was preferred in the laser‐prepared fluorosed enamel in terms of bonding performance. Microsc. Res. Tech. 77:779–784, 2014. © 2014 Wiley Periodicals, Inc.